Dependence of anodic titanium (IV) oxide properties on activator composition - Дементий, Андрей Владимирович (Technology audit and production reserves, 2013)
The process of obtaining a secondary carrier of catalytically active substance for its application in catalysis was considered and some results of our research in this field were given. The main objective of the study is to examine the dependence of properties of titanium (IV) oxide, obtained by anodization method, on the activator composition. Porous titanium (IV) oxide layer was obtained by titanium plate anodizing in electrolyte consisting of aqueous solutions of sulfuric acid and activator. By changing the activator composition its effect on the properties of secondary carrier and optimal anodizing time was studied. The presented method allows estimating the dependence of thickness and porosity of the obtained secondary carrier and optimal anodization time on the activator composition. The results of the study can be used in electrochemistry and catalysis for improving the process of obtaining secondary carrier forcatalytically active substances. We propose to improve the process of getting secondary carrier for catalytically active substances on the surface of titanium plate using more efficient activator.